DEBT SECURITY INDICATORS OF THE NATIONAL ECONOMY BANKING SECTOR - Cоловаров Андрій (Socio-economic relations in the digital society, 2019)
The approaches to assessing the level of debt security of the banking sector of the national economy are investigated. Th e necessity of compliance with the debt security of the banking sector is substantiated. The methods for assessing the level of debt security are described. The expediency of defi ning the threshold values of debt security indicators of the banking sector by rationing is indicated. Th e views of researchers on the list of debt security indicators of the banking sector and empirical research on this issue, conducted in foreign countries, as well as the negative consequences of non-compliance with the threshold values of indicative indicators, are analyzed. It is an early warning of the coming systemic banking crises. Th e author’s vision of debt security indicators of the banking sector of the national economy is presented. Th e need to assess the level of debt security of the banking sector to take into account the scale of the negative consequences of not investing it in the threshold values.